Inclusion of rare taxa from Blattidae and Anaplectidae improves phylogenetic resolution in the cockroach superfamily Blattoidea. (15th January 2023) - Deng, Wenbo; Luo, Xinxing; Ho, Simon Y. W.; Liao, Shuran; Wang, Zongqing; Che, Yanli
Abstract: Cockroaches are an ecologically and economically important insect group, but some fundamental aspects of their evolutionary history remain unresolved. In particular, there are outstanding questions about some of the deeper relationships among cockroach families. As a group transferred from Blaberoidea Saussure to Blattoidea Latreille, the evolutionary history of the family Anaplectidae Walker requires re‐evaluation. In our study, we infer the phylogeny of Blattoidea based on the mitochondrial genomes of 28 outgroup taxa and 67 ingroup taxa, including 25 newly sequenced blattoid species mainly from the families Anaplectidae and Blattidae Latreille. Our results indicate that Blattoidea is the sister group of the remaining Blattodea Brunner von Wattenwyl and that Blattoidea can be divided into three main clades: Blattidae + Tryonicidae McKittrick & Mackerras, Lamproblattidae McKittrick + Anaplectidae and Termitoidae Latreille + Cryptocercidae Handlirsch. Our analyses provide robust support for previously uncertain hypotheses. The sister group of Termitoidae + Cryptocercidae (Xylophagodea Engel) is inferred to constitute the rest of Blattoidea, for the first time. Within Blattidae, Hebardina Bey‐Bienko is placed as the sister lineage to the rest of Blattidae. The subfamily Archiblattinae is polyphyletic, Blattinae is paraphyletic and Polyzosteriinae is monophyletic (Macrocercinae Roth not included); the genus Periplaneta Burmrister is polyphyletic. Based on the results of our phylogenetic analyses, we have revised these taxa. A new subfamily, Hebardininae subfam.nov., is proposed in Blattidae. Archiblattinae and Shelfordella Adelung are synonymized with Blattinae and Periplaneta, respectively: Archiblattinae Kirby syn.nov. and Shelfordella Adelung syn.nov. Our inferred divergence times indicate that Blattoidea emerged in the Late Triassic, with six families in Blattoidea diverging in the Middle and Late Jurassic. We suggest that the divergences among lineages of Asian Blattidae and Anaplectidae were driven by the uplift of the Himalayas and deglaciation during the Quaternary, leading to the present‐day distributions of these taxa. Abstract : 1. Phylogeny reconstruction based on mitochondrial genomes provided a number of insights into the evolutionary history of Blattoidea. 2. A new subfamily and two synonyms were proposed in Blattidae: Hebardininae subfam. nov., Archiblattinae Kirby syn. nov. and Shelfordella Adelung syn. nov. 3. The divergence and modern distribution of Asian Blattidae and Anaplectidae species was driven by the uplift of the Himalayas and deglaciation during the Quaternary.